MoM antenna simulations, with Matlab RWG basis functions. - Makarov, Sergey (IEEE Antennas & propagation magazine.)
The Matlab implementation of an MoM antenna simulation code is presented, primarily (but not exclusively) for educational purposes. The PDE toolbox is used to generate the mesh. Evaluating the MoM matrix entries using the Rao-Wilton-Glisson (RWG) basis functions is discussed. The delta-function generator is used to model the feed point. Built-in Matlab functions are used for post-processing. Results for several examples, including thin-strip dipoles, a monopole on a ground plane and a wide-band slot antenna, are presented.